Watching Women: Surveillance and Spectatorship in Early Science Fiction Television. - Dickason, Cara (Camera Obscura, 2024)
This article analyzes episodes of early science fiction anthology series to examine how fears of television's ability to turn its gaze on the home circulated around women, both as objects of surveillance and as television spectators, in the 1950s and 1960s. Media historians have called attention to the importance of women in defining the role of new technologies and have detailed the gendered popular constructions of early television. This article stems from such work, addressing the time when audiences and producers alike were grappling with the imagined potential of television's visuality and liveness to impose visibility on its viewers. Early episodes of Tales of Tomorrow, The Twilight Zone, and The Outer Limits expose anxieties about the power of television as a surveillance mechanism to enact control over audiences. Formally and narratively, these episodes complicate the division between seeing and being seen, particularly for women viewers, while enacting strategies to contain and discipline women. They mobilize women's navigation of visual subjectivity and objectification only to eschew their ability to look and reify their status as objects to be looked at. By taking a closer look at early television surveillance narratives, this article demonstrates how women's television spectatorship has always entailed a complex negotiation of imposed looking relations that paradoxically attempt to deny the female gaze even as they depend on it. Understanding this historical context helps illuminate the gendered power dynamics of spectatorship and visibility in our present media landscape, in which the convergence of TV and surveillance technologies realizes the imagined fears of the mid-twentieth century.